Interaction between warfarin and short-term intravenous amiodarone in intensive care unit patients after cardiac surgery - Tomoki Takase; Hiroaki Ikesue; Makiko Tohi; Hiroshi Ueta; Hiroyuki Mima; Tadaaki Koyama; Tohru Hashida (BMC, 2018)
Abstract Background Amiodarone and warfarin are sometimes administered immediately after cardiac surgery. Although the interaction between long-term oral amiodarone and warfarin has been reported, the interaction between warfarin and short-term intravenous amiodarone has not been reported. In this study, we investigated the effect of short-term intravenous amiodarone on the anticoagulant effect of warfarin in patients who underwent cardiac surgery. Methods We retrospectively reviewed the medical records of 11 patients who received oral warfarin before and after cardiac surgery, and loading doses of 125-150 mg or a 750 mg continuous infusion of amiodarone, or both in the intensive care unit (ICU) within 5 days after the surgery between July 2011 and January 2017. The prothrombin time-international normalized ratio (PT-INR)/daily warfarin dose (PT-INR/dose) was used as an indicator of anticoagulant effect. The values before surgery were considered as the baseline. Results The PT-INR and PT-INR/dose values were elevated in 7 and 10 patients, respectively, after amiodarone administration. The mean PT-INR values were not significantly different before and after amiodarone administration (2.13 ± 0.58 vs 2.29 ± 0.50, respectively, p = 0.643). In contrast, the mean PT-INR/dose values were significantly elevated after the administration of amiodarone (0.93 ± 0.46 vs 1.54 ± 0.63, respectively, p = 0.002). Conclusions Short-term intravenous amiodarone enhanced the anticoagulant effect of warfarin in patients admitted to the ICU after cardiac surgery. We suggest that the dose of warfarin should be carefully adjusted for a few days after cardiac surgery if intravenous amiodarone is coadministered.